2014
DOI: 10.1088/0004-637x/795/2/116
|View full text |Cite
|
Sign up to set email alerts
|

The Puzzling Negative Orbit-Period Derivative of the Low-Mass X-Ray Binary 4u 1820-30 in NGC 6624

Abstract: 4U 1820-30 is a low-mass X-ray binary near the center of the globular cluster NGC 6624 consisting of, at least, one neutron star and one helium white dwarf. Analyzing 16 years of data from the Rossi X-ray Timing Explorer (RXTE) allows us to measure its orbital period and its time derivative with unprecedented accuracy to be P = 685.01197 ± 0.00003 s andṖ /P = −5.3 ± 0.3 × 10 −8 yr −1 . Hence, we confirm that the period derivative is significantly negative at the > 17σ level, contrary to theoretical expectation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 63 publications
5
51
0
Order By: Relevance
“…We note that the enclosed mass within the radius of the MSP is lower than the inferred IMBH mass of Perera et al (2017a): M(< 0.41 ) = 646 +74 −163 M (and in three dimensions: M(< 0.41 ) = 362 +93 −199 M ). We therefore agree with the conclusion of Peuten et al (2014) that NGC 6624 has a population of centrally concentrated dark remnants. However, these authors did not present dynamical models.…”
Section: Discrete Modelssupporting
confidence: 92%
See 1 more Smart Citation
“…We note that the enclosed mass within the radius of the MSP is lower than the inferred IMBH mass of Perera et al (2017a): M(< 0.41 ) = 646 +74 −163 M (and in three dimensions: M(< 0.41 ) = 362 +93 −199 M ). We therefore agree with the conclusion of Peuten et al (2014) that NGC 6624 has a population of centrally concentrated dark remnants. However, these authors did not present dynamical models.…”
Section: Discrete Modelssupporting
confidence: 92%
“…A convincing signal of an IMBH would be a measure of the gravitational acceleration in its vicinity, which can be obtained with timing observations. Peuten et al (2014) analysed the orbital period, P orb , of the low-mass X-ray binary (LMXB) 4U 1820-30 that sits at 1.3 from the centre in projection of the bulge GC NGC 6624. If there are no intrinsic binary processes changing the orbital period, then the period derivate,Ṗ orb , is due to a gravitational acceleration along the line-of-sight (a los ), which contributes toṖ orb asṖ orb /P = a los /c (Blandford et al 1987;Phinney 1993), where c is the speed of light and we assumed that a positive a los implies an acceleration away from the observer.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we cannot exclude the existence of an additional source near the centre of the globular cluster (located at 18:23:40.51, -30:21:39.7 ± 0.1 , Goldsbury et al 2010), which is not resolved within the ALMA or ATCA beams (see, e.g. Peuten et al 2014, for suggestions of a large number of dark remnants in the central region of the cluster). Such potential source could significantly contribute at the ALMA band but not at the radio or X-ray bands, which would remain dominated by the emission from 4U 1820−30.…”
Section: U 1820−30mentioning
confidence: 98%
“…We therefore conclude that the mass fraction of stellar-mass black holes that we found from the N-body models is, within the model uncertainties, in agreement with the expected fraction based on recent models for the evolution of massive stars. Peuten et al (2014) analysed 16 yr of timing data of the low-mass X-ray binary (LMXB) 4U 1820-30 that is located close to the centre of NGC 6624 and found that this LMXB has a strongly negative period derivative. They suggested that an acceleration of the star along the line of sight due to either a dark concentration of remnants or an IMBH could be responsible for creating this period change.…”
Section: Implication For the Initial Stellar-mass Black Hole Retentiomentioning
confidence: 99%